Characterising the hydration process of cement slurry system based on low-field NMR. Issue 1 (27th June 2018) - Huo, Jin-hua; Peng, Zhi-gang; Ye, Zhongbin; Feng, Qian; Zheng, Yong; Zhang, Jian
Abstract : As a non-destructive and non-invasive technique with high stability and continuity, low-field nuclear magnetic resonance (low-field NMR) was used to characterise the initial hydration process of cement slurry systems based on grade G oil well cement, which is widely used in various cementing operations, and microfine cement, which is playing an increasingly important role as a reinforcing material, especially in the field of low-temperature cementing. The initial hydration process of the cement slurry systems was investigated using the Carr–Purcell–Meiboom–Gill (CPMG) technique. This method was used as it has the advantage over other spin echo techniques in that it allows rapid multiple accumulations of the echo train signal, which is an important issue in increasing detection sensitivity at low fields. The transverse relaxation time ( T 2 ) distribution curve and CPMG echo train of the cement slurry systems were first obtained. Then, the initial hydration process of grade G oil well cement and microfine cement was characterised by using the peak area and the value and distribution of T 2 . The results showed that the low-field NMR has great potential in the characterisation of the hydration process of cement-based materials.